Distribution and quantification of lymphocytes in the major lymphoid organs of naturally gumboro infected broilers - Mohammad Mejbah Uddin; Mohammad Saiful Islam; Joyita Basu; Md. Zahirul Islam Khan (2012)
Gumboro disease is caused by the infectious bursal disease virus (IBDV) which rapidly destroys immature B- lymphocytes of bursa of Fabricious, and causes immune suppression and high mortality in commercial broiler farms in Bangladesh. To